(untitled) (Research, Society and Development, 2020)
Arterial hypertension (AH) is a chronic disease, determined by pressure levels above 140/90 mm/Hg. Data from the Ministry of Health (MS) reveal that more than 30 million Brazilians suffer from diagnosed AH and it is estimated that more than half are unaware of the presence of the disease or do not undergo treatment. The present study aimed to assess the prevalence of hypertensive patients treated by dental clinics at UNIPAR, as well as to review the literature on oral alterations caused by the use of antihypertensive drugs and the use of local anesthetics (LA) with or without vasoconstrictor (VS). Cross-sectional/prevalence study, where the research was carried out at the dental clinics of UNIPAR campus Cascavel, where volunteers were instructed to complete a structured form referring to their systemic condition, novice and hygiene habits, the data obtained were tabulated and submitted to statistical analysis. Of the 854 volunteers, 57.25% (n = 489) had no systemic changes, 42.74% (n = 365) had systemic changes, of which 38.22% (n = 133) individuals had hypertension. It can be concluded that the dental surgeon (CD) within this context has an important role in the diagnosis of patients with this condition, since the vast majority are unaware of having the disease. The prevalence of hypertensive patients seeking dental care is relatively high. In addition, it is important to control the patient’s anxiety, whether orally or inhaled, have good anesthetic technique and care in the choice of medications that will be used in the postoperative period.